Parent Involvement Through a Practice Theory Lens - Janet Goodall (Education Sciences, 2025)
This paper suggests the use of practice theory as a lens for considering the interactions between parents (or those acting as the main support for children) and school staff. Practice theory, arising from separate strains of philosophy, was first used to look at parental engagement by Spear et al. in relation to children in designated special schools. In this paper, we expand on their previous work, widening the application of practice theory to interactions between all parents and school staff. This paper examines the concepts of parental involvement and engagement, and of practice theory itself. It highlights the importance of school culture related to the interactions between school staff and parents, and then concentrates on the two main themes arising from practice theory: actions create society, and those actions then create the architectures in which actions take place. This highlights the possibilities of change. The final section of this paper sets out the parameters schools can use to scaffold these processes of change, suggesting that the two groups (parents and staff) be considered instead as members of one group, ‘adults supporting learning’.